Beyond the sacro-Iliac joints: Vertebral involvement in axial spondylarthritis. Issue 144 (November 2021) - Rahimi, Hamza; Guermazi, Ali; Roemer, Frank W.; Teytelboym, Oleg M.; Carlier, Robert-Yves; Jarraya, Mohamed
Highlights: Vertebral involvement of axial spondylarthritis can occur without sacroiliitis. Spinal inflammatory changes may involve the vertebral corners, intervertebral discs, posterior elements, facet joints, and ligamentous insertions. The primary role of magnetic resonance imaging is to support establishing a diagnosis of axial spondylarthritis by typical imaging findings and to monitor therapeutic response. Abstract: Imaging plays a central role in the diagnosis of axial spondylarthritis (axSpA). Commonly the sacroiliac joints are involved but vertebral involvement can occur in isolation in 1 out of 4 patients. Recognizing vertebral involvement patterns in axSpA can help establishing a diagnosis early and initiate therapy before irreversible changes have occurred. Magnetic resonance imaging (MRI) is considered the reference standard for early detection of inflammatory changes of the disease. Aims of this review are to present an overview of the imaging findings of vertebral involvement in axSpA, and to detail the current recommendations on the role of imaging in the diagnosis of axSpA in patients with isolated vertebral involvement.